An exploration of food and the lived experience of individuals after treatment for colorectal cancer using a phenomenological approach. Issue 2 (26th January 2015) - Burden, S. T.; Stamataki, Z.; Hill, J.; Molasiotis, A.; Todd, C.
Abstract: Background: There is a paucity of qualitative literature investigating people's experiences of food and nutrition after treatment for cancer. The present study aimed to explore people's relationships with food and nutrition throughout their colorectal cancer journey. Methods: In‐depth semi‐structured interviews were conducted with 25 participants who had undergone surgery for colorectal cancer. The study design was informed by principles of phenomenology. Data were collected then transcribed and analysed using an inductive coding process and a thematic analysis to allow the themes to highlight people's lived experiences. Results: Data enabled five primary themes to be drawn including: 'appetite swings', 'emotions on a changing physicality', 'the medicalisation of food', 'taking control of symptom management' and a cross‐cutting theme 'drivers and vehicles for action'. Feelings and emotions described by participants around their relationship with food and nutritional status often guided decisions on what was eaten more than objective nutritional measure or dietary advice. Participants used weight changes, appetite and food as barometers to measure their overall recovery. Food was an area over which people exhibited control of their lives and they could quantify, in measurable units, their overall well‐being and rehabilitation. They did this either by using the currency of body weight in pounds or the size of portions eaten. Conclusions: Appetite, weight and symptoms influenced dietary intake substantially and were poignant issues affecting people's lives. The relationship people have with food determines their eating habits and an understanding of the essences and nuances of their experiences is essential to enable the delivery of patient‐centred care.